PENGARUH LITERACY CLOUD TERHADAP MINAT BACA DAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS IV SD - Dewa Made Dwicky Putra Nugraha (Jurnal Elementary:Kajian Teori dan Hasil Penelitian Pendidikan Sekolah Dasar, 2023)
This study aimed at determining (1) the effect of cloud literacy on the students’ reading interest at fourth grade of SDN 2 Sayan, (2) the effect of cloud literacy on students’ comprehension reading skills at fourth grade of SDN 2 Sayan, (3) the effect of cloud literacy simultaneously on reading interest and comprehension reading skills for grade IV SDN 2 Sayan. This research was an experimental research with all fourth grade students of SDN 2 Sayan as population, which consisted of 53 students divided into 2 groups, namely IV A and IV B classes. The sample of this research was determined through random sampling technique. IV A Class as the sample of the experimental group with a sample of 27 people, while IV B class as the control class as many as 26 people. The data on reading interest and comprehension reading skills used questionnaires and essay tests. The data were analyzed using MANOVA assisted by SPSS 2.1 for windows. The results showed that 1) there was a significant difference in reading interest of the students who learned by using cloud literacy applications with the students who learned without using cloud literacy, 2) there was significant differences in reading comprehension skills of students who learned by using cloud literacy applications with students who learned without using cloud literacy, 3) there was a significant effect of the implementation of cloud literacy on the students’ reading interest and comprehension reading skills at fourth grade of SDN 2 Sayan simultaneously.